Intraspecific variation in an Ediacaran skeletal metazoan: Namacalathus from the Nama Group, Namibia. Issue 1 (28th September 2016) - Penny, A. M.; Wood, R. A.; Zhuravlev, A. Yu.; Curtis, A.; Bowyer, F.; Tostevin, R.
Abstract: Namacalathus hermanastes is one of the oldest known skeletal metazoans, found in carbonate settings of the terminal Ediacaran (~550–541 million years ago [Ma]). The palaeoecology of this widespread, goblet‐shaped, benthic organism is poorly constrained yet critical for understanding the dynamics of the earliest metazoan communities. Analysis of in situ assemblages from the Nama Group, Namibia (~548–541 Ma), shows that Namacalathus exhibited size variation in response to differing water depths, hydrodynamic conditions and substrate types. In low‐energy, inner ramp environments, Namacalathus attains the largest average sizes but grew in transient, loosely aggregating, monospecific aggregations attached to microbial mats. In high‐energy mid‐ramp reefs, Namacalathus spatially segregated into different palaeoecological habitats with distinct size distributions. In outer ramp environments, individuals were small and formed patchy, dense, monospecific aggregations attached to thin microbial mats. Asexual budding is common in all settings. We infer that variations in size distribution in Namacalathus reflect differences in habitat heterogeneity and stability, including the longevity of mechanically stable substrates and oxic conditions. In the Nama Group, long‐lived skeletal metazoan communities developed within topographically heterogeneous mid‐ramp reefs, which provided diverse mechanically stable microbial substrates in persistently oxic waters, while inner and outer ramp communities were often ephemeral, developing during fleeting episodes of either oxia and/or substrate stability. We conclude that Namacalathus, which forms a component of these communities in the Nama Group, was a generalist that adapted to various palaeoecological habitats within a heterogeneous ecosystem landscape where favourable conditions persisted, and was also able to opportunistically colonise transiently hospitable environments. These early skeletal metazoans colonised previously unoccupied substrates in thrombolitic reefs and other microbial carbonate settings, and while they experienced relatively low levels of interspecific competition, they were nonetheless adapted to the diverse environments and highly dynamic redox conditions present in the terminal Ediacaran.